Large universe decentralized key-policy attribute-based encryption - Li, Qi; Ma, Jianfeng; Li, Rui; Xiong, Jinbo; Liu, Ximeng (Security and communication networks, 2015)
In multi‐authority attribute‐based encryption (ABE) systems, each authority manages a different attribute universe and issues the private keys to users. However, the previous multi‐authority ABE schemes are subject to such restrictions during initializing the systems: either the attribute universe is polynomially sized and the attributes have to be enumerated or the attribute universe can be exponentially large, but the size of the set of attributes, which will be used in encryption, is not more than a predefined fixed value. These restrictions prevent multi‐authority ABE schemes from being deployed in dynamic practice applications. In this paper, we present a large universe decentralized key‐policy ABE scheme without such additional limitation. In our scheme, there is no requirement of any central authority. Each attribute authority executes independently from the others and can join or depart the system allodiality. Our system supports any monotone access policy. The proposed scheme is constructed on prime order groups and proved selectively secure in the standard model. To the best of our knowledge, our scheme is the first large universe decentralized key‐policy ABE system in the standard model. Copyright © 2014 John Wiley & Sons, Ltd. Our contributions review current multi‐authority attribute‐based encryption schemes and demonstrate the restrictions in the initial phase, present a new decentralized key‐policy attribute‐based encryption scheme, which can support large attribute universe without such restrictions, and performance comparison and security proof indicate that our scheme is efficient and secure.